Pengaruh Ketidakpastian Lingkungan dan Sistem Informasi Akuntansi Manajemen terhadap Kinerja Manajerial - Lella Anita (Budgeting: Jurnal Akuntansi Syariah, 2023)
The purpose of this study is to investigate and offer empirical data on the relationship between management accounting information systems and environmental uncertainty in relation to managerial performance. In this study, questionnaires were filled out as part of the survey method of data collecting. 50 middle and low level managers from banks and non-bank financial firms in Metro City and East Lampung made up the study's population. Purposive sampling was utilized during sampling. Structural Equation Model (SEM) with the Partial Least Square (PLS) application program version 4.0.m is the analysis method employed. The study's findings demonstrate that (1) there is no relationship between environmental uncertainty and managerial performance, contradicting the hypothesis. (2) The qualities of information integration significantly improve managerial effectiveness. Meanwhile, managerial performance is unaffected by the information qualities of broad scope, timeliness, and aggregation.